Spectrum performance of PTM modulation techniques - Ho, Raymond Weng Kiong. (2009)
Optical fiber networks are being widely used to provide broadband telecommunication services which multiplexes video (video-telephone, video-conference), data and voice channels. The choice of modulation format on the optical carrier is therefore a principal factor in realizing a high-performance bandwidth-efficient system at an acceptable cost. Even though the bandwidths offered by new fiber network installations are very high they are still limited by fiber dispersion and carrier incoherent over practical distances.